Use of Cost-Effectiveness Analyses for Decisions About Vaccination Programs for Meningococcal Disease in the United States, United Kingdom, The Netherlands, and Canada. (2nd January 2021) - Huang, Liping; Mauskopf, Josephine; Farkouh, Ray; Masaquel, Catherine
ABSTRACT: Introduction: Meningococcal vaccines to protect against invasive meningococcal disease (IMD) vary in terms of vaccine technology and serogroup coverage (Polysaccharide MnACWY, conjugated C and ACWY, outer membrane vesicle–based or protein-based B vaccines), and the national recommendations for each of them vary in terms of target population and number of doses. We sought to understand factors associated with the evolution of meningococcal vaccination program recommendations in four countries with formal evaluation processes: the UK, US, the Netherlands, and Canada. Areas covered: A targeted review of published literature and internet sources for the four countries relating to meningococcal vaccination decision-making was conducted. The review focused on the impact of cost-effectiveness analyses on vaccine policy decisions and the extent to which variation in incidence of IMD and its potential catastrophic consequences influenced policy decisions. The evolution of meningococcal vaccine recommendations in the four countries was mainly driven by changes in vaccine availability and changes in serogroup incidence. Public pressure due to the catastrophic nature of IMD influenced recommendations. The role of cost-effectiveness analyses varied across the 4 countries. Expert Opinion: The value of implementing meningococcal vaccination programs should be assessed using factors beyond those included in traditional cost-effectiveness analyses.